The Tourism Industry as a Tool for Local Economic Development of the Territorial Communities of the Carpathian Region of Ukraine - Pavliuk Svitlana; Mirzayev Natig; Ungalov Sanjar (BIO Web of Conferences, 2025)
Tourism, as an important part of social progress, not only contributes to economic growth but also has the potential to catalyze changes in socio-cultural and ecological dimensions. The relevance of the topic of tourism as a tool for the local economic development of territorial communities of the Carpathian region of Ukraine is due to the following: tourism is a factor in economic growth, which contributes to the creation of new jobs, attracting investments and increasing the level of well-being of the population. Tourism affects the preservation and dissemination of cultural heritage, stimulates interest in preserving natural resources and ecosystems, and promotes understanding, tolerance, and environmental awareness. In challenging conditions such as martial law or other difficult situations, tourism can be a source of profit and a tool for the reconstruction and development of regions in need of support. The purpose of the article is to identify the trend of tourism development in the Carpathian region, its role and significance for local economic development, and on this basis to justify the advantages of their synergistic relationship. The research uses a set of scientific research methods of a general nature (analysis and synthesis, induction and deduction, abstraction, formalization) and a special one (content analysis, comparison, graphic), which made it possible to reveal meaningful interpretations of regularities regarding the understanding of the concepts of «local economic development» and «creative tourism» as well as characterize the synergistic relationship between them. It was established that the Carpathian region has significant tourism potential, and the dynamics of tax revenues from the tourism industry in the Lviv, Ivano- Frankivsk, Zakarpattia, and Chernivtsi regions show a positive result. The Ukrainian and world scientists` works were analyzed regarding the impact of tourism on the local economic development of territorial communities, as a result of which attention was focused on several advantages in the economy, socio-cultural sphere, and ecology.